2016
DOI: 10.1007/s00404-016-4033-x
|View full text |Cite
|
Sign up to set email alerts
|

Women show a higher level of anxiety during IVF treatment than men and hold different concerns: a cohort study

Abstract: Women show a higher level of anxiety during IVF treatment and hold different concerns. Neither of the sexes appears to be familiar with the risks associated with multiple pregnancies, a matter that should better be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 19 publications
4
37
1
Order By: Relevance
“…Moreover, the level of anxiety increased during the Paulina Gdańska et al, Anxiety and depression in women undergoing infertility treatment www. journals.viamedica.pl/ginekologia_polska course of infertility treatment [13]. Some other studies also found a relationship between the duration of infertility and increased level of anxiety [11,22].…”
Section: The Influence Of Infertility and Art Procedures On Anxietymentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, the level of anxiety increased during the Paulina Gdańska et al, Anxiety and depression in women undergoing infertility treatment www. journals.viamedica.pl/ginekologia_polska course of infertility treatment [13]. Some other studies also found a relationship between the duration of infertility and increased level of anxiety [11,22].…”
Section: The Influence Of Infertility and Art Procedures On Anxietymentioning
confidence: 93%
“…A study by Kahyaoglu Sut et al showed that undergoing infertility treatment was related to a lower quality of life and a higher level of anxiety in a study group of 89 women [21]. One of the studies carried on the German population found that both women and men had a higher level of anxiety compared to the general population and women had a higher anxiety level compared to men [13]. Moreover, the level of anxiety increased during the Paulina Gdańska et al, Anxiety and depression in women undergoing infertility treatment www.…”
Section: The Influence Of Infertility and Art Procedures On Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies examining the effect of involuntary childlessness and infertility treatment on psychological well-being in men and women have concluded that women suffer greater emotional consequences than men (18,21,22,31,34,36,(45)(46)(47)(48). However, some studies have found men to be greatly affected by the consequences of infertility and its treatment, perhaps as much as women (49)(50)(51).…”
Section: Involuntary Childlessness Infertility and Psychological Welmentioning
confidence: 96%
“…shown that involuntary childlessness and infertility increase levels of stress (19,(21)(22)(23), symptoms of depression (21,(24)(25)(26)(27)(28)(29)(30)(31)(32) or anxiety (24)(25)(26)(27)(32)(33)(34)(35) and have a negative effect on quality of life (33,36), mental health (37) and sexual relations (25, 38). Others have found equal or lower levels of anxiety (22, 39, 40), depression (22, 39-41) and psychological distress (22, 42) and no differences in relationship quality (39,43) or sexual satisfaction (39) in involuntarily childless or infertile individuals compared to reference groups.…”
Section: Involuntary Childlessness Infertility and Psychological Welmentioning
confidence: 99%